Prognostic value of sarcopenia in patients with liver cirrhosis: A systematic review and meta-analysis. - Gaeun Kim; Seong Hee Kang; Moon Young Kim; Soon Koo Baik (PLoS ONE)
Background Sarcopenia is a common syndrome in chronic diseases such as liver cirrhosis. The association between sarcopenia and outcomes, such as complications and survival has recently been described in various patient groups. However, study results remain inconclusive. Therefore, the aim of this study was to systematically review the impact of sarcopenia on outcome in patients with cirrhosis. Methods and findings We conducted a systematic review (SR) and meta-analysis (MA) on the impact of sarcopenia on outcome in liver cirrhosis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Of the 312 studies identified, 20 were eligible according to our inclusion criteria. Most of the studies used CT to diagnose sarcopenia. Two studies used bioelectrical impedance analysis (BIA), 10 studies used skeletal muscle index (SMI) and 8 studies used total psoas muscle area (TPA). Seven studies included Asian participants and the remaining 13 studies included Western participants. The prevalence rate of sarcopenia among participants was mean 48.1%, and appeared more among men with a rate of 61.6% whereas the rate was 36% for women. With respect to clinical outcomes, patients with sarcopenia had poorer survival rates and an increased risk of complications such as infection compared to those without sarcopenia. According to the analysis of race subgroup, Asians had a HR 2.45 (95% confidence interval (CI) = 1.44-4.16, P = 0.001) of mortality whereas Westerners had a HR 1.45 (95% CI = 1.002-2.09, P<0.05). Conclusions Based on this SR and MA, the presence of sarcopenia is related to a poor prognosis and occurrence of cirrhotic complications and could be used for risk assessment. Moreover, Asian participants had higher mortality related to sarcopenia compared to the Western participants.